Pengaruh Penggunaan Absensi Finger Print dan Motivasi Terhadap Disiplin Pegawai Pada Diklat Provinsi Sumatera Selatan (Jurnal Manajemen dan Investasi (MANIVESTASI), 2019)
Â Influence of Finger Print And Motivation on Employee Discipline Training South Sumatra province, the problem is 1). Is there a significant influence on the use of Finger Print Employee Discipline Training Sumatra province. 2). Is there a significant influence Motivation on Employee Discipline Training Sumatra province. 3) Is there a significant influence and use Finger Print Motivation on Employee Discipline Training Sumatra province.The analysis technique used consists of validity, reliability test, classical test covering normality test, multicollinearity, heteroscedasticity test, simple linear regression analysis, multiple linear regression analysis, t test, F test, the coefficient of determination, hypothesis testing. Results of the analysis results obtained by simple linear regression equation of Use Finger Print (X1) Y '= 22.261 + 0,802X1 and motivation (X2) variable Y' = 22.261 + 0,894X2. While persamaanan multiple linear regression is Y '= 22.261 + 0,802X1 + 0,894X2. Values thitung X1 = 2.714> 1.987 ttabel means of Use Finger Print partial significantly influence employee Discipline. For thitung X2 = 2.426> 1.987 ttabel. This means that the partial effect on the motivation of employees Discipline. Test F together (simultaneously) and the test results showed that the numbers sig 0.000